Mechanical Properties of PCL/PLA Composite Sample Produce from 3D Printer and Injection Molding - Abdul Haq, Reazul Haq; Taib, Ishkrizat; Abdol Rahman, Mohd Nasrull; Fu Haw, Ho; Abdullah, Haslina; Ahmad, Said; Tajul Ariffin, Ahmad Mubarak; Hassan, Mohd Fahrul (International Journal of Integrated Engineering, 2019)
Currently there are a lot of studies have been carried out regarding on composite material that can be used for 3D printing. The main reasons is to minimize the cost related to the molds that need to be prepared for injection molding. The question is how far will be the differences in term of mechanical properties for part produce from this 2 techniques. This study are done to investigate the mechanical properties of PCL/PLA composite sample prepared from Fused Deposition Modelling (FDM) 3D printer. The mechanical properties that were evaluated are tensile, flexural and impact. The result were later compared with samples produced from injection molding. The dimensional accuracy result shows a very minimal percentage error on samples produced using 3D printer for mechanical testing. The parameter of 3D printer used to produce sample was 136Â°C print temperature, 0.12mm deposition of height, 20mm/s print speed and 22mm/s travel speed. The mechanical properties of PCL/PLA prepared by injection molding generally came superior in all the conducted test if compared to those of 3D printer. Tensile strength result showed that injection molding value was higher than 3D printer which is 10MPa and 6.513MPa respectively. The results of tensile strength and modulus of elasticity showed injection molding ware better than 3D printing with value of 118.26MPa and 61.223MPa respectively. For flexural strength, the highest values were injection molding which is 7.59MPa while 3D printing is 4.96Mpa. While the highest for flexural modulus are 35.33GPa for injection molding and 30.911GPa for 3D printing. Impact strength for PCL/PLA sample was 1.33 Joule for injection molding and 0.543 Joule for 3D printer method.